Lack of acute phase response in the livers of mice exposed to diesel exhaust particles or carbon black by inhalation - Saber, Anne T (BioMed Central, 2009)
BACKGROUND: Epidemiologic and animal studies have shown that particulate air pollution is associated with increased risk of lung and cardiovascular diseases. Although the exact mechanisms by which particles induce cardiovascular diseases are not known, studies suggest involvement of systemic acute phase responses, including C-reactive protein (CRP) and serum amyloid A (SAA) in humans. In this study we test the hypothesis that diesel exhaust particles (DEP) – or carbon black (CB)-induced lung inflammation initiates an acute phase response in the liver. RESULTS: Mice were exposed to filtered air, 20 mg/m(3 )DEP or CB by inhalation for 90 minutes/day for four consecutive days; we have previously shown that these mice exhibit pulmonary inflammation (Saber AT, Bornholdt J, Dybdahl M, Sharma AK, Loft S, Vogel U, Wallin H. Tumor necrosis factor is not required for particle-induced genotoxicity and pulmonary inflammation., Arch. Toxicol. 79 (2005) 177–182). As a positive control for the induction of an acute phase response, mice were exposed to 12.5 mg/kg of lipopolysaccharide (LPS) intraperitoneally. Quantitative real time RT-PCR was used to examine the hepatic mRNA expression of acute phase proteins, serum amyloid P (Sap) (the murine homologue of Crp) and Saa1 and Saa3. While significant increases in the hepatic expression of Sap, Saa1 and Saa3 were observed in response to LPS, their levels did not change in response to DEP or CB. In a comprehensive search for markers of an acute phase response, we analyzed liver tissue from these mice using high density DNA microarrays. Globally, 28 genes were found to be significantly differentially expressed in response to DEP or CB. The mRNA expression of three of the genes (serine (or cysteine) proteinase inhibitor, clade A, member 3C, apolipoprotein E and transmembrane emp24 domain containing 3) responded to both exposures. However, these changes were very subtle and were not confirmed by real time RT-PCR. CONCLUSION: Our findings collectively suggest that Sap, Saa1 and Saa3 are not induced in livers of mice exposed to DEP or CB. Despite pulmonary inflammation in these mice, global transcriptional profiling of liver did not reveal any hepatic response following exposure by inhalation.